P55 Syngenic bone marrow transfer stimulates hepatic progenitor cell expansion via TWEAK/Fn14 Signalling: implications for human autologous cell therapy. (16th November 2010) - Bird, T; Knight, B; Boulter, L; Gordon-Keylock, S; Wjotacha, D; Thomas, J; Sansom, O; Iredale, J; Forbes, S
Abstract : Introduction: Autologous bone marrow cell (BMC) therapy for liver disease has shown increased liver regeneration in animal studies and in phase 1 clinical studies. As yet no clear mechanism accounts for these observations. BMCs do not directly form into hepatocytes but can improve liver regeneration and function. In chronic liver disease hepatic progenitor cells (HPCs) are a potential source of parenchymal regeneration. Whilst the transplantation of human HPCs is not currently a practical therapeutic option, manipulating endogenous HPCs in vivo represents a potential approach. HPCs exist in a specialised niche of leukocytes and mesenchymal cells, which secrete cytokines that are capable of regulating HPC behaviour. We therefore hypothesised that infusion of BMC into the liver may induce HPC expansion via paracrine signalling. Aim: To investigate the effect of autologous BMC infusion upon regeneration by hepatic progenitor cells. Method: 107 syngenic BMCs were infused into healthy mice by tail vein, we examined intrahepatic donor cell engraftment, cytokine expression, liver function tests, and HPC activation. Cell tracking utilised either GFP+ or male cells delivered into female wild type mice. Whole liver and specific cell fractions were analysed by immunocytochemistry, in-situ hybridisation, FACS, and qRT-PCR. Results: Following BMC transfer, a progressive and sustained expansion of HPCs was observed (mean±SEM 41.9±2.1 cells per field vs PBS control 23.5±4.1 at 21 days post infusion, p=0.003) with associated increase in liver/body weight ratio (BMC 0.0513±0.001 vs PBS control 0.0470±0.001, p=0.022). BMCs engrafted the liver adjacent to HPCs for up to 3 weeks and were mostly F4/80+ macrophages (81%). Transfer of F4/80+ macrophages alone into healthy mice recapitulated the HPC expansion. Cytokine gene expression analysis revealed one soluble signal in particular, TWEAK, increased in the recipient's liver following donor BMC engraftment (5.20-fold induction vs control at Day 3). Extracted donor derived BMCs expressed TWEAK, as do macrophages. TWEAK is known to be a direct mitogen to HPCs via the Fn14 receptor. When Fn14-/- mice were used as recipients to wild type BMC infusions the expansion of HPCs was entirely lost (mean±SEM 27.2±1.4 vs negative PBS control 30.6±2.4, p=0.128 vs positive wild-type control 42.7±2.3, p=0.0002), demonstrating that the HPC expansion is dependent on TWEAK-Fn14 paracrine signalling between BMCs and HPCs. Conclusion: These data describe a hitherto unknown mechanism by which infused autologous macrophages signal in a paracrine manner to HPCs via TWEAK. These observations suggest potential for the development of novel therapies to promote human liver regeneration.